Synthesis new derivatives of Azo compounds contain a Schiff bases and evaluate their biological activity - Khadm, Nada Jaffar; Shannak, Qader Abdullah; Ibraheem, Tareq K. (Edelweiss Applied Science and Technology, 2024)
The novel compounds have been synthesis via reaction benzidiene compund with p-amino acetophenone in the presence of ethanol absolute and reflux with stirrer to give Schiff base compound 1. The Schiff base copound treated with phosphoric acid and nitric acid, sodium nitrate and o-hydroxynaphthaldehyde, to product Azo compound 2. This compound reaction with different aromatic amines such as 2-chloro aniline, 4-hydroxyaniline, 2-carboxyaniline, 3-hydroxyaniline respectively to give compounds 3a-d. All the new compounds characterized by FT-IR spectrophotometer and HNMR spectroscopy, and evaluation The synthesized compounds shown moderate to good effectiveness against both gram positive (Streptococcus pneumoniae, Mycobacterium tuberculosis) and gram negative (Esherichia coli, Proteus mirabilis) bacteria when compared to the original medication.